The next CEO : board and CEOperspectives for successful CEO succession - Keil, Thomas, 1970 February 6- author.; Zangrillo, Marianna, author. (Milton Park, Abingdon, Oxon ; New York, NY : Routledge, 2021)
"Every year, companies spend billions of dollars in board time and headhunter fees on CEO search. In fact, by many accounts, the selection of the next CEO is the single most important task of the board of directors. Yet, despite the huge amount of time, money, and attention given to the task, many CEO changes fail, with disastrous consequences for all concerned. With so much at stake, it is natural to ask what companies and their boards can do to increase the odds of success. Illustrated with an abundance of real-life examples from interviews with CEOs, C-Suite members, members of the boards, and headhunters supporting CEO search, The Next CEO explains how boards can improve the odds of success with CEO succession by identifying clear CEO mandates, associated CEO profiles, and by selecting CEOs that are fit for purpose. It further explains how the CEOs of leading corporations effectively take charge and create results, providing a roadmap for incoming CEOs. These ideas are brought to life with case studies and interviews with well-known corporations such as ABB, Alibaba, Freudenberg, GE, Google, HNA, HP, Microsoft, Nestle, Nike, Nokia, Novartis, Roche, Sony, Tata, and Zurich Insurance. The book is invaluable practical reading for Board members of medium to large sized firms involved with CEO succession, and for those preparing for their first CEO position. It is also relevant to headhunters who are involved in the process of CEO succession as a working tool for them and their clients. In addition, the book will be relevant to courses on Corporate Governance and Strategic Transformation at the Executive and MBA level"--